Edible oils as a co-extractant for the supercritical carbon dioxide extraction of flavonoids from propolis - Pattiram, Parveen Devi; Abas, Faridah; Suleiman, Norhidayah; Mohamad Azman, Ezzat; Gun, Hean Chong (Public Library of Science, 2022)
Propolis is a good source for flavonoids, however, their recovery is challenging, as it is a waxy material. This study investigated edible oils virgin coconut oil (VCO), corn oil (CO), and ghee (G) as co-extractants for the supercritical carbon dioxide (scCO2) extraction of flavonoids from the propolis. The extraction of flavonoids using 20% VCO as co-extractant with scCO2 (25 g/min) for 210 min at 150 bar and 50°C was found to be the most appropriate, yielding a total flavonoid content (TFC) of 11.7 mg/g and 25% TFC recovery. At a higher temperature (60°C) and pressure (250 bar and 350 bar), the propolis became softer and compressed causing the extractions to retrograde. The extraction curves correlated to the diffusion model with 1.6% (AARD). The matrix diffusivities increased from 4.7 × 10−11 m2/s (scCO2) to 6.9 × 10−11–21.4 × 10−11 m2/s upon the addition of edible oils. Thus, edible oils could be used with scCO2 to improve the flavonoid extraction from propolis.